1996
DOI: 10.1016/0735-1097(95)00596-x
|View full text |Cite
|
Sign up to set email alerts
|

Collateral channels that develop after an acute myocardial infarction prevent subsequent left ventricular dilation

Abstract: Collateral channels that develop after a myocardial infarction do not reduce the infarct size or prevent left ventricular dilation within 1 month of infarction. In contrast, such collateral channels prevent subsequent ventricular dilation and the deterioration of left ventricular function over 2 years. However, our results may have been biased because of the small number of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 32 publications
1
32
0
1
Order By: Relevance
“…Myocardial ischemia provides a potent stimulus to angiogenesis and the subsequent development of collateral vasculature that maintains and/or revitalizes cardiac tissue. [1][2][3][4][5] The mobilization and differentiation of bone marrow-derived endothelial progenitor cells (EPCs) has recently been shown to be important in this process of adult neovascularization. 6 -10 Evidence suggests that EPCs contribute as much as 25% of endothelial cells (ECs) in newly formed blood vessels, 11 and transplantation of EPCs into patients has been demonstrated to induce blood flow recovery in ischemic limbs 12 and increase myocardial viability after infarction.…”
mentioning
confidence: 99%
“…Myocardial ischemia provides a potent stimulus to angiogenesis and the subsequent development of collateral vasculature that maintains and/or revitalizes cardiac tissue. [1][2][3][4][5] The mobilization and differentiation of bone marrow-derived endothelial progenitor cells (EPCs) has recently been shown to be important in this process of adult neovascularization. 6 -10 Evidence suggests that EPCs contribute as much as 25% of endothelial cells (ECs) in newly formed blood vessels, 11 and transplantation of EPCs into patients has been demonstrated to induce blood flow recovery in ischemic limbs 12 and increase myocardial viability after infarction.…”
mentioning
confidence: 99%
“…[1][2][3][4] In younger individuals, myocardial ischemia induces the development of a collateral supply that partially protects the cardiac tissue from subsequent coronary events. [5][6][7][8] However, angiogenesis is impaired in the cardiac 4,9 -13 and peripheral vascular beds of older individuals, 14,15 and this defect may underlie the increased severity of cardiovascular disease in the geriatric population. Therefore, elucidation of the cellular and molecular pathways that are impaired with aging is critical for developing specific strategies to prevent and reduce the pathogenesis of cardiovascular disease associated with advancing age.…”
mentioning
confidence: 99%
“…5 These clinical conditions are also accompanied by EDNO deficiency. 15 Endothelial nitric oxide is a key contributor to angiogenesis, as a downstream mediator of growth factor(s).…”
Section: Optimization Of Gene Delivery To Ischemic Hindlimb Musculaturementioning
confidence: 99%
“…5 In the presence of cardiovascular risk factors, including advanced age, angiogenesis is impaired, which may contribute to the increased severity of cardiovascular diseases in this patient population. [6][7][8][9][10] Studies in experimental mouse models of hindlimb ischemia demonstrated impaired revascularization and CLI like symptoms (i.e.…”
Section: Introductionmentioning
confidence: 99%